Działania z zakresu ratownictwa społecznego w Polsce w latach 1944–1948 - Brenk, Mikołaj (My University, 2014)
The article concerns the field of social care and social assistance in the first years of the People’s Republic of Poland provided to individuals who suffered distress during World War Two. The timeline of the paper covers the years 1944-1948. At that time, the focus of social care and social assistance was satisfying the fundamental needs of the people, in particular in environments affected by the destruction of war. It included, among others, ensuring food, health care, accommodation, education and employment. The scale of the relief provided after the war by various Polish and international institutions was unprecedented in the history of the Polish social service with one in four Poles involved i.e. over 6 million people in total.
Social response in Poland in the years 1944–1948
Keywords: human services; relief provided after the war; social care; social assistance